2021
DOI: 10.5547/01956574.42.6.akha
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Risk for Financial Institutions in the Major Petroleum-based Economies: The Role of Oil

Abstract: We examine the relationship between oil returns and systemic risk of financial institutions in major petroleum-based economies. By estimating ACoVaR, we observe the presence of remarkable increases in risk levels during the financial crises and achieve a better risk measurement when oil returns are included in the risk functions. Moreover, the estimated spread between the CoVaR without and with oil returns is absorbed in a time range that is longer than the duration of the oil shocks. This indicates that drops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Also, they discussed how the financialization of crude oil markets affects oil market functionality and efficiency. Khalifa et al (2021) examined the relationship between oil returns and systemic risk of financial institutions in major petroleumbased economies. By estimating Delta CoVaR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, they discussed how the financialization of crude oil markets affects oil market functionality and efficiency. Khalifa et al (2021) examined the relationship between oil returns and systemic risk of financial institutions in major petroleumbased economies. By estimating Delta CoVaR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lupu et al (2021) found that European energy companies enhanced systemic risk spillovers during 2008, early 2009, and 2020. Within the oil and gas sector, the ∆CoV aR has been used in Khalifa et al (2021) to evaluate the role of oil in driving the systemic risk of the Gulf Cooperation Countries' financial markets, while Tiwari et al (2020) used ∆CoV aR and MES to show that oil price dynamics contribute significantly more to G7 stock market returns during volatile times than during tranquil times. 5 Al-Jarrah et al (2021) show that traditional models fail to capture the systemic risk of small-middle size banks operating in the Gulf Cooperation Council since they have high levels of economies of scale.…”
Section: Literature Background and Institutional Frameworkmentioning
confidence: 99%
“…. Some examples of analysis of the tail dependence structure in energy markets can be found inKim and Jung (2018),Khalifa et al (2021), andRahman et al (2022).…”
mentioning
confidence: 99%